Climate-Related Financial Disclosures : Thematic Module in the Integrated State-Owned Enterprises Framework (iSOEF) - World Bank (Washington, DC, 2022)
The current iSOEF provides guidance on assessing SOE performance in an economy. Thisincludes the rationale for SOEs and their economic outcomes, operational efficiency, and corporate governance, as well as effective government oversights on these enterprises and options for reforming the sector. The iSOEF takes a modular approach, allowing for a flexible application according to the specific country context and development needs. Modules 1–4 address the role of SOEs in the market, their fiscal and distributional implications, and their corporate governance and accountability mechanisms. Module 5 takes a sectoral perspective, focusing on state-owned financial institutions. Finally, three thematic modules address cross-cutting factors, such as corruption risks, political economy considerations, and communication strategies. Each module contains additional analytical tools, matrices, questionnaires, key indicators, and other analytical instruments to be used for diagnostics and assessment. This diagnostic matrix proposes the inclusion of (i) a new thematic module in the iSOEF to facilitatean assessment and consideration of climate-related management and financial disclosure, and(ii) a question on climate-related financial disclosures under Module 4: Financial Accountability,Controls, and Transparency, or “non-financial reporting.”. This latter question is appropriateto indicate the scope of the non-financial reporting concept and to ensure that the iSOEF isadequately addressing it in both theory and practice. This diagnostic matrix is structured as follows. Chapter 1 sets the scene on why SOE regulators and SOEs should focus on climate change, why a diagnostic matrix is essential, and why a separate thematic module. Chapter 2 sets out the iSOEF Thematic Module on SOE Climate Related Financial Disclosures, articulating the specific assessment steps.